O Método em Marx e a Pesquisa Social: https://doi.org/10.60543/ts_iss.vi10.10805 ("Temas Sociais" Journal, 2026)
This essay is part of the assessment activities of the course “Social Work: Theoretical-Methodological Foundations and Intervention in Reality – Contemporary Debate”, offered by a Graduate Program in Social Work in northern Brazil. Its object of study is the method in Marx, understood within the framework of historical-dialectical materialism, aiming to discuss its centrality in social research and, particularly, in Social Work research, highlighting fundamental categories and theoretical assumptions. Methodologically, this is a theoretical essay of a critical-dialectical nature, based on a theoretical-critical bibliographic review, emphasizing classical works by Karl Marx and authors from the Marxian tradition. As its main theoretical contribution, the article reaffirms the centrality of the critical-dialectical method in the production of social knowledge, emphasizing its conception of totality and the criterion of truth grounded in the unity between theory and practice, as essential mediations for an analytical perspective committed to the emancipatory character of theory.
Keywords: Marx’s Method; Social Research; Criterion of Truth; Theory–practice Unity